Improving Programming Learning in Engineering Students through Discovery Learning - Aldalur, Inigo; Sagarna, Xabier (IEEE-RITA, 2023)
Programming is basic to all engineering studies and a complicated subject for many first-year students. Many of the problems stem from the difficulty students have in finding the solution they need on the Internet, which makes students more dependent on the lecturer. Add to this the need for students to use new technologies in the classroom and the rapid digitization caused by the COVID-19 pandemic, the use of the Discovery Learning through WebQuests instructional model is of great help to students. For this subject, students are required to learn C programming using Visual Studio. The results show that WebQuests have contributed to improve academic results and skills such as teamwork, motivation and imagination to solve the problems posed. Students find themselves able to think of appropriate solutions, sometimes more than one solution, and carry them out. In addition, students conclude that the WebQuests have helped them to use their imagination, generate creative ideas and increase their ability to put what they have learned into practice.